Age of Methylphenidate Treatment Initiation in Children With ADHD and Later Substance Abuse: Prospective Follow-Up Into Adulthood - Mannuzza, Salvatore; Klein, Rachel G.; Truong, Nhan L.; Moulton, John L.; Roizen, Erica R.; Howell, Kathryn H.; Castellanos, Francisco X. (The American journal of psychiatry, 2008)
Objective: Animal studies have shown that age at stimulant exposure is positively related to later drug sensitivity. The purpose of this study was to examine whether age at initiation of stimulant treatment in children with attention deficit hyperactivity disorder (ADHD) is related to the subsequent development of substance use disorders. Method: The authors conducted a prospective longitudinal study of 176 methylphenidate-treated Caucasian male children (ages 6 to 12) with ADHD but without conduct disorder. The participants were followed up at late adolescence (mean age=18.4 years; retention rate=94%) and adulthood (mean age=25.3; retention rate=85%). One hundred seventy-eight comparison subjects also were included. All subjects were diagnosed by blinded clinicians. The Cox proportional hazards model included the following childhood predictor variables: age at initiation of methylphenidate treatment, total cumulative dose of methylphenidate, treatment duration, IQ, severity of hyperactivity, socioeconomic status, and lifetime parental psychopathology. Separate models tested for the following four lifetime outcomes: any substance use disorder, alcohol use disorder, non-alcohol substance use disorder, and stimulant use disorder. Other outcomes included antisocial personality, mood, and anxiety disorders. Results: There was a significant positive relationship between age at treatment initiation and non-alcohol substance use disorder. None of the predictor variables accounted for this association. Post hoc analyses showed that the development of antisocial personality disorder explained the relationship between age at first methylphenidate treatment and later substance use disorder. Even when controlling for substance use disorder, age at stimulant treatment initiation was significantly and positively related to the later development of antisocial personality disorder. Age at first methylphenidate treatment was unrelated to mood and anxiety disorders. Conclusions: Early age at initiation of methylphenidate treatment in children with ADHD does not increase the risk for negative outcomes and may have beneficial long-term effects.